2023
DOI: 10.3390/ijms242216040
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells in the Pathogenesis and Therapy of Autoimmune and Autoinflammatory Diseases

Lina N. Zaripova,
Angela Midgley,
Stephen E. Christmas
et al.

Abstract: Mesenchymal stem cells (MSCs) modulate immune responses and maintain self-tolerance. Their trophic activities and regenerative properties make them potential immunosuppressants for treating autoimmune and autoinflammatory diseases. MSCs are drawn to sites of injury and inflammation where they can both reduce inflammation and contribute to tissue regeneration. An increased understanding of the role of MSCs in the development and progression of autoimmune disorders has revealed that MSCs are passive targets in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 186 publications
0
2
0
1
Order By: Relevance
“…Mesenchymal stromal cells represent a population of multipotent progenitor stromal cells characterised by their capacity for self-renewal. Upon exposure to the appropriate stimuli, MSCs can differentiate into various specialised cell lineages derived from the mesenchyme, such as osteocytes, chondrocytes, myocytes, tenocytes, and ligamentocytes [ 4 , 5 ]. The human zygote-stage embryo displays totipotent characteristics, enabling the generation of both embryonic and extraembryonic tissues [ 6 ].…”
Section: Mesenchymal Stromal Cells—sources and Regenerative Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stromal cells represent a population of multipotent progenitor stromal cells characterised by their capacity for self-renewal. Upon exposure to the appropriate stimuli, MSCs can differentiate into various specialised cell lineages derived from the mesenchyme, such as osteocytes, chondrocytes, myocytes, tenocytes, and ligamentocytes [ 4 , 5 ]. The human zygote-stage embryo displays totipotent characteristics, enabling the generation of both embryonic and extraembryonic tissues [ 6 ].…”
Section: Mesenchymal Stromal Cells—sources and Regenerative Propertiesmentioning
confidence: 99%
“…MSCs can recruit and regulate T cells through both direct cell-to-cell contact and paracrine signalling pathways. The paracrine effects of MSCs are attributed to the release of various molecules, such as growth factors, cytokines with anti-inflammatory properties, chemokines, and extracellular vesicles containing bioactive components, such as non-coding RNA (ncRNA) [ 4 , 18 , 19 , 20 ]. Additional research has also demonstrated that extracellular vesicles released by stem cells (MSC-EVs) exhibit immunosuppressive and immunomodulatory characteristics [ 21 , 22 , 23 , 24 ].…”
Section: Mesenchymal Stromal Cells—sources and Regenerative Propertiesmentioning
confidence: 99%
“…2020)sugere especialmente que a IL-17A como possível biomarcador de atividade de doenças autoimunes sistêmicas.Outra abordagem no tratamento de pacientes com doenças autoimunes destacam as células-tronco mesenquimais (MSCs) devido às suas propriedades imunomoduladoras e capacidades regenerativas. As MSCs têm o potencial de suprimir respostas imunológicas, reduzir inflamações e contribuir para a regeneração tecidual(Zaripova et al, 2023).Uma pesquisa conduzia por Cavalcante (2020) destaca o potencial terapêutico das células-tronco mesenquimais. Essa modalidade de tratamento, apresenta benefícios potenciais, como a produção em larga escala.…”
unclassified